Rapid Automatic Cacao Pod Borer Detection Using Edge Computing on Low-End Mobile Devices - Eros Allan Somo Hacinas; Lorenzo Sangco Querol; Kris Lord T. Santos; Evian Bless Matira; Rhodina C. Castillo; Mercedes Arcelo; Divina Amalin; Dan Jeric Arcega Rustia (Agronomy, 2024)
The cacao pod borer (CPB) (Conopomorpha cramerella) is an invasive insect that causes significant economic loss for cacao farmers. One of the most efficient ways to reduce CPB damage is to continuously monitor its presence. Currently, most automated technologies for continuous insect pest monitoring rely on an internet connection and a power source. However, most cacao plantations are remotely located and have limited access to internet and power sources; therefore, a simpler and readily available tool is necessary to enable continuous monitoring. This research proposes a mobile application developed for rapid and on-site counting of CPBs on sticky paper traps. A CPB counting algorithm was developed and optimized to enable on-device computations despite memory constraints and limited capacity of low-end mobile phones. The proposed algorithm has an F1-score of 0.88, with no significant difference from expert counts (R2 = 0.97, p-value = 0.55, <semantics>α</semantics> = 0.05). The mobile application can be used to provide the required information for pest control methods on-demand and is also accessible for low-income farms. This is one of the first few works on enabling on-device processing for insect pest monitoring.